Торцовый электромашинный генератор - Кац М. Д. Марк Давыдович; Кляйн Р. Я. Роберт Яковлевич; Попов В. И. Виталий Иванович; Сипайлов Г. А. Геннадий Антонович; Юнда Н. И. Николай Иванович
опубл. 07.11.91